2001
DOI: 10.1046/j.1460-9592.2001.00692.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect on intraocular pressure of tracheal intubation or laryngeal mask™ insertion during sevoflurane anaesthesia in children without the use of muscle relaxants

Abstract: Sevoflurane does not prevent the increase in IOP after intubation without muscle relaxants. LMA does not increase IOP in children after sevoflurane induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 19 publications
2
17
0
1
Order By: Relevance
“…Holden et al 16 were the first one to compare the IOP changes using LMA and endotracheal tube and their observations as well as those of Lamb et al 17 revealed a significantly smaller increase in IOP using LMA both on placement and removal as compared to endotracheal intubation. Similar results were reported by Whitford et al 18 and Duman et al 19 The I-GEL is a new supraglottic device without an inflatable cuff, designed for use during anaesthesia. 20 It is a latex free, disposable device, made of a medical grade thermoplastic elastomer.…”
Section: Discussionsupporting
confidence: 84%
“…Holden et al 16 were the first one to compare the IOP changes using LMA and endotracheal tube and their observations as well as those of Lamb et al 17 revealed a significantly smaller increase in IOP using LMA both on placement and removal as compared to endotracheal intubation. Similar results were reported by Whitford et al 18 and Duman et al 19 The I-GEL is a new supraglottic device without an inflatable cuff, designed for use during anaesthesia. 20 It is a latex free, disposable device, made of a medical grade thermoplastic elastomer.…”
Section: Discussionsupporting
confidence: 84%
“…Duman et al. (19) reported that IOPs have not been changed with sevoflurane without using a muscle relaxant.…”
Section: Discussionmentioning
confidence: 99%
“…Eltzschig et al (18) reported minimal decrease after induction with sevoflurane, but they used rocuronium, a muscle relaxant. Duman et al (19) reported that IOPs have not been changed with sevoflurane without using a muscle relaxant.…”
Section: Discussionmentioning
confidence: 99%
“…10 17 21 22 Outcome measures of early childhood glaucoma are different from those of adult or adolescent patients because the IOP may not be reliable; several factors can influence the IOP reading, because the child is distressed at the time of taking the pressure awake or because the child is under anaesthesia, giving an artefactual result. [23][24][25] Also reliable sequential visual field monitoring is not always possible as in our cases. For this reason the whole picture-that is, corneal clarity, horizontal corneal diameter, cup-disc ratio, refraction and/or axial length must be taken into account.…”
Section: Discussionmentioning
confidence: 99%